Gathering communities: locality, governance and rulership in early medieval Ireland. Issue 1 (1st January 2018) - Gleeson, Patrick
ABSTRACT: This article explores the role that gatherings and temporary assembly places played in creating communities and manufacturing early polities and kingdoms. Whereas the archaeological dimension to polity building has often focused upon monumentality in programmes of political articulation, the role of more ephemeral activities is equally meaningful but nevertheless under-appreciated. With new research into assembly culture in first-millennium AD Europe developing apace, the role of gatherings of various types has come into sharper focus. This article explores the changing nature of temporary gatherings in Ireland and what the changing material signature of these practices says about developing hierarchies, emerging kingdoms and the nexus that local concerns formed with regional practices of rulership.